POLA KOMUNIKASI ORGANISASI DALAM IMPLEMENTASI PROGRAM MERDEKA BELAJAR KAMPUS MERDEKA (MBKM) DAN PRAKTEK KERJA LAPANGAN (PKL) DI GREEN SCHOOL BALI - Suparna, Putu; Pratiwi, Nuning Indah; Lestari, Ni Kadek Devy (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
Complex and extensive communication within an organization will create a pattern of communication that becomes the flow of information being channel. This pattern of communication will make it easier for students to determine appropriate and correct actions and directions. The purpose of this study is to examine how the Green School Bali's pattern of organizational communication is implemented to students of the PKL and MBKM internship programs using Goldhaber's (1986) theory of organizational communication, which describes seven key concepts: process, message, network, interdependence, relationship, environment, and uncertainty. The research method used was a qualitative one involving observations and in-depth interviews with informants, who in this study were supervisors of each department, heads of internships, and student interns for the July-December 2022 period. The results of this study indicate that Green School Bali uses the wheel organizational communication pattern in its implementation for apprentice students in the PKL and MBKM programs.